Light‐Tunable Generation of Singlet Oxygen and Nitric Oxide with a Bichromophoric Molecular Hybrid: a Bimodal Approach to Killing Cancer Cells. (5th November 2015) - Fraix, Aurore; Blangetti, Marco; Guglielmo, Stefano; Lazzarato, Loretta; Marino, Nino; Cardile, Venera; Graziano, Adriana C. E.; Manet, Ilse; Fruttero, Roberta; Gasco, Alberto; Sortino, Salvatore
Abstract: The design, synthesis, photochemical properties, and biological evaluation of a novel photoactivatable bichromophoric conjugate are reported. The compound1, [4‐(4, 4‐difluoro‐2, 6‐diiodo‐1, 3, 5, 7‐tetramethyl‐4‐bora‐3a, 4a‐diaza‐ s ‐indacen‐8‐yl)‐ N ‐(3‐((4‐nitro‐3‐(trifluoromethyl)phenyl)amino)propyl)butanamide] combines a 2, 6‐diiodo‐1, 3, 5, 7‐tetramethyl BODIPY derivative as singlet oxygen ( 1 O2 ) photosensitizer and 4‐nitro‐3‐(trifluoromethyl)aniline (NOPD) as nitric oxide (NO) photodonor, joined by an alkyl spacer. These two chromogenic units absorb in distinct regions of the visible spectrum, and their individual photochemical properties are conserved in the molecular conjugate. Irradiation of the bichromophoric conjugate with green light afforded 1 O2 in high quantum yields, whereas 1 O2 production was negligible with the use of blue light; under this latter condition, NO was released. Photogeneration of NO and cytotoxic 1 O2 can therefore be regulated by appropriately tuning the excitation light wavelength and intensity. Tested on melanoma cancer cells, this resulted in amplified photomortality relative to that of a structurally correlated model compound2 [4‐(4, 4‐difluoro‐2, 6‐diiodo‐1, 3, 5, 7‐tetramethyl‐4‐bora‐3a, 4a‐diaza‐ s ‐indacen‐8‐yl)‐ N ‐(3‐( p ‐tolylamino)propyl)butanamide] deprived of the NO‐release capacity. The cellular uptake of1, evaluated by confocal fluorescence microscopy, showed that the product is localized in the cytoplasm. Abstract : Two‐pronged zapping : A bichromophoric molecular hybrid was synthesized by combining a tailored BODIPY derivative as singlet oxygen ( 1 O2 ) photosensitizer with a nitroaniline derivative as nitric oxide (NO) photodonor. These two chromogenic units absorb in distinct regions of the visible spectrum, and thus photogeneration of the cytotoxic 1 O2 and NO species can be regulated by appropriately tuning the excitation light. This bimodal action amplifies the photomortality of melanoma cancer cells.